2019
DOI: 10.1139/anc-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study on tides in the Port of Vancouver

Abstract: In the present paper, tides in the port of Vancouver Harbour have been investigated with a high-resolution three-dimensional hydrodynamic model based on FVCOM (Finite Volume Community Ocean Model). The model was evaluated against field observations including tidal elevations and tidal currents, and the evaluation showed that the model was in good agreement with the observational data. Using the model, we first investigated the horizontal distributions of tides, tidal currents, and tidally induced residual circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Foreman et al (2012) investigated the tidal circulation in the Discovery Island region of British Columbia. Using FVCOM, two regional tidal models were developed in the Hecate Strait (Wu et al, 2017) and the Vancouver Harbor (Wu et al, 2019), respectively. In the Canadian Arctic Archipelago (CAA) and Baffin Bay, Guo et al (2020) reported the use of a tidal model for the summer season.…”
Section: R a F Tmentioning
confidence: 99%
“…Foreman et al (2012) investigated the tidal circulation in the Discovery Island region of British Columbia. Using FVCOM, two regional tidal models were developed in the Hecate Strait (Wu et al, 2017) and the Vancouver Harbor (Wu et al, 2019), respectively. In the Canadian Arctic Archipelago (CAA) and Baffin Bay, Guo et al (2020) reported the use of a tidal model for the summer season.…”
Section: R a F Tmentioning
confidence: 99%
“…Tidal waves are obviously deformed when prograding into Vancouver Harbour due to highly rugged coastline and bathymetry. Using a higher resolution model based on FVCOM (finite volume community ocean model) with a flexible triangle mesh system, Wu et al (2019) investigated tidal processes in the harbor. The modeled tidal amplitude and current matched very well with the observed data.…”
Section: Estuarine Hydrodynamic Alterations and Regime Shiftmentioning
confidence: 99%
“…FVCOM allows the use of different resolutions to fit complex coastline and topography by using the triangle mesh system. The model used in the present study was based on the model set up by Wu et al [26]. The model was capable of achieving relatively high resolution in the region of interest (English Bay and Vancouver Harbour in this case), as shown in Figure 3.…”
Section: Fvcom Descriptionmentioning
confidence: 99%
“…The vertical grid has twenty-one sigma levels that were stretched gradually, in order to gain higher resolution in the surface and bottom layers. More detailed information of the model can be found in Wu et al [26]. [8].…”
Section: Fvcom Descriptionmentioning
confidence: 99%
See 1 more Smart Citation